Is Article 8(3) EUTMR applicable only to identical marks and identical goods? 'No', says the Court of Justice. (6th September 2021) - Martin, Stefan; Boyd, Jonathan
Abstract: Court of Justice of the European Union, MINERAL MAGIC/MAGIC MINERALS BY JEROME ALEXANDER et al, C-809/18 P, EU: C:2020:902, 11/11/2020 The Court of Justice provides clear guidance on the test to be applied under Article 8(3) of the EU Trade Mark Regulation 2017/1001 ('EUTMR).